Assessment of plant growth promoting activities of bacterial isolates from the rhizophere of tomato (Lycopersicon esculentum. L) - D. Reetha, S. Mahalakshmi (Recent Research in Science and Technology, 2009)
Plant growth promoting bacteria in the rhizosphere of plants, enhanced plant growth by exerting their beneficial effects through metabolites that directly or indirectly influence the plant growth. In the present study a total of 44 bacterial isolates were isolated from the rhizosphere of tomato grown in Cuddalore and Nagapattinam districts of Tamil Nadu, India. These bacterial isolates were grouped into Azospirillum (18 isolates) Azotobacter (9) Pseudomonas (12) and Bacillus (5) based on their morphological and biochemical characteristics. All the isolates were screened for their plant growth promoting activities viz., IAA production, phosphate solubilization, siderophore production, HCN production, ACC deaminase activity and antifungal activity. The results showed that not all the isolates possessed all the PGP activities. The range of percentage of positive isolates of Azospirillum, Azotobacter, Pseudomonas and Bacillums for each of PGP activities varies greatly. Among the 44 isolates, three isolates of Azospirillum, 2 from Azotobacter, one from Bacillus and four from Pseudomonas were selected and the IAA production siderophore production, and antifungal activity against R. solani and Fusarium oxysporum were determined quantitatively. The maximum 1AA production of 3.6 g/ml siderophore production of 0.86 g/ml were recorded by TMPS-9 and TMPS-7 respectively. All the tested isolates were active against the two fungal species. The efficiency of the PGPR isolates should be tested under field conditions in the rhizosphere of tomato to obtain a suitable consortium for increasing growth and yield of tomato.